Male Disadvantage in Undergraduate Ob/Gyn Learning and its Consequences: Experience of Malaysian Private and Public Medical Students - Nurfatini Irdina Muhammad Sharidan; Nur Syaza Nasuha Mohd Isa; Nurfariha Effendy; Hanis Athirah Azhab; Saw Ohn Mar (Asian Journal of Medicine & Health Sciences, 2023)
Background: There are several concerns regarding the quality of male medical students’ learning experience and their clinical skills development in Obstetrics and Gynaecology (Ob/Gyn) that may lead to clinical incompetency and lack of interest in the specialty. Objectives: This study aimed to evaluate male gender specific problems in undergraduate Ob/Gyn learning and their effects. It also determined the association between the limitations in clinical skill exposure and their clinical skill development and confidence level. Methods: Self-administered questionnaire-based survey was conducted involving 99 male medical students, who completed their Ob/Gyn rotation, from a public and a private medical university. Results: The largest proportion of participants experienced patient refusal “sometimes” for performing abdominal examination (35.4%), and observing pelvic examination and procedures (35.4%), observing or assisting normal delivery (37.4%) and even for their presence during consultation (51.5%) although they faced less refusal for history taking and observing LSCS. The highest proportion of the respondents exhibited “high confidence” in antenatal history taking (56.6%), gynaecological history taking (47.5%) and performing Leopold’s manoeuvre (35.4%). However, proportion of respondents who expressed “low confidence” for performing obstetric vaginal examination and Pap smear were 38.4% and 32.3% respectively. Although 45.4% of respondents expressed less interest in pursuing Ob/Gyn career after their rotation, 43.5% would still consider Ob/Gyn as their future profession. The mean scores for limitations in learning, confidence level, and perceived effect on career choice were not significantly different between private and public university students. Our analysis also showed that the students with limitations in clinical learning are seven times more likely to have low confidence (OR 7.358, 95% CI 3.0018.03). Conclusion: Significant degree of male disadvantage was observed in undergraduate Ob/Gyn learning that may have a substantial impact on their clinical competency and their interest selecting O&G speciality. Our results highlight the need for learning support systems by lecturers, female friends, and faculty to provide better learning experience for male students in Ob/Gyn posting.